2008
DOI: 10.1007/s11096-008-9213-8
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related problems: evaluation of a classification system in the daily practice of a Swiss University Hospital

Abstract: We consider the PCNE system to be a practical tool in the hospital setting, which demonstrates the values of a clinical pharmacy service in terms of identifying and reducing DRPs and also has the potential to reduce prescribing costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
2
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 19 publications
5
45
2
11
Order By: Relevance
“…This reflects the typical focus areas of rational pharmacotherapy in the elderly and in polypharmacy patients [9,54,55] and is similar to other studies classifying DRPs with the PCNE classification [9,56,57]. The typical approach has to be changed in more than just the timing when performing medication review in the acute ward setting.…”
Section: Interventionssupporting
confidence: 70%
See 2 more Smart Citations
“…This reflects the typical focus areas of rational pharmacotherapy in the elderly and in polypharmacy patients [9,54,55] and is similar to other studies classifying DRPs with the PCNE classification [9,56,57]. The typical approach has to be changed in more than just the timing when performing medication review in the acute ward setting.…”
Section: Interventionssupporting
confidence: 70%
“…The majority of hospitalised patients have drug-related problems (DRPs) [1][2][3][4][5][6][7][8][9][10][11] which are events or circumstances involving drug therapy that actually or potentially can interfere with the desired health outcomes [12]. The total cost of drug-related morbidity and mortality exceeds the cost of the medications themselves [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown drug-related problems (DRPs) to be very common in primary care and in hospital settings [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. In both settings there is evidence that pharmacists' interventions can reduce the occurrence of DRPs [6,9,14,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…ABD'de, yılda en az 1,5 milyon hasta, aslında önlenebilecek olan advers ilaç olaylarından zarar görmekte ve bunların tedavisi her yıl en az 3,5 milyar dolara mal olmaktadır 4, . İlaçla ilgili problemler, farklı gruplar tarafından farklı sınıflandırmalar altında kategorize edilseler de, ilaç hataları, advers ilaç reaksiyonları ve advers ilaç olayları bu kapsamın içindedir [5][6][7][8] . Hastanelerde görülen advers olayların %10.8-%37.…”
Section: Introductionunclassified